The P2X7 Receptor Mediates Toxoplasma gondii Control in Macrophages through Canonical NLRP3 Inflammasome Activation and Reactive Oxygen Species Production - Moreira-Souza, Aline Cristina Abreu; Almeida-da-Silva, Cássio Luiz Coutinho; Rangel, Thuany Prado; Rocha, Gabrielle da Costa; Bellio, Maria; Zamboni, Dario Simões; Vommaro, Rossiane Claudia; Coutinho-Silva, Robson (Frontiers in Immunology, 2017)
Toxoplasma gondii is the protozoan parasite that causes toxoplasmosis, a potentially fatal disease to immunocompromised patients, and which affects approximately 30% of the world’s population. Previously, we showed that purinergic signaling via the P2X7 receptor contributes to T. gondii elimination in macrophages, through ROS production and lysosome fusion with the parasitophorous vacuole. Moreover, we demonstrated that P2X7 receptor activation promotes the production of anti-parasitic pro-inflammatory cytokines during early T. gondii infection in vivo. However, the cascade of signaling events that leads to parasite elimination via P2X7 receptor activation remained to be elucidated. Here, we investigated the cellular pathways involved in T. gondii elimination triggered by P2X7 receptor signaling, during early infection in macrophages. We focused on the potential role of the inflammasome, a protein complex that can be co-activated by the P2X7 receptor, and which is involved in the host immune defense against T. gondii infection. Using peritoneal and bone marrow derived macrophages from knockout mice deficient for inflammasome components (NLRP3-/-, Caspase-1-/-, Caspase-11-/- and Caspase-1/11-/-), we show that the control of T. gondii infection via P2X7 receptor activation by eATP depends on the canonical inflammasome effector caspase-1, but not on caspase-11 (a non-canonical inflammasome effector). Parasite elimination via P2X7 receptor and inflammasome activation was also dependent on ROS generation and pannexin-1 channel. Treatment with eATP increased IL-1β secretion from infected macrophages, and this effect was dependent on the canonical NLRP3 inflammasome. Finally, treatment with recombinant IL-1β promoted parasite elimination via mitochondrial ROS generation (as assessed using Mito-TEMPO). Together, our results support a model where P2X7 receptor activation by eATP inhibits T. gondii growth in macrophages by triggering NADP oxidase-dependent ROS production, and also by activating a canonical NLRP3 inflammasome - which increases IL-1β production (via caspase-1 activity), leading to mitochondrial ROS generation.